Global Transcriptomic Analyses Reveal Genes Involved in Conceptus Development During the Implantation Stages in Pigs - Zang, Xupeng; Gu, Ting; Hu, Qun; Xu, Zhiqian; Xie, Yanshe; Zhou, Chen; Zheng, Enqin; Huang, Sixiu; Xu, Zheng; Meng, Fanming; Cai, Gengyuan; Wu, Zhenfang; et al. (Frontiers in Genetics, 2021)
Prenatal mortality remains a significant concern to the pig farming industry around the world. Spontaneous fetal loss ranges of 20 to 45% by term occur after fertilization, with most of the loss happening during the implantation period. Since the factors regulating high mortality rates of early conceptus during implantation phases are poorly understood, we sought to analyze the overall gene expression changes during this period, and identify the molecular mechanisms involved in conceptus development. This work employed Illumina’s next-generation sequencing (RNA-Seq) and quantitative real-time PCR (qRT-PCR) to analyze differentially expressed genes (DEGs). Soft clustering was subsequently used for cluster analysis of gene expression. We identified 8236 DEGs in porcine conceptus at day 9, 12, and 15 of pregnancy. Annotation analysis of these genes revealed rRNA processing (GO:0006364), cell adhesion (GO:1904874) and heart development (GO:0007507), as the most significantly enriched biological processes at day 9, 12 and 15 of pregnancy, respectively. In addition, we found various genes, such as TCP1, RUVBL2, CTGF, ITGs, IFNG, SLA-1, CXCL9, PAG-2, TGFBR1, and ANXA2, that play essential roles in conceptus morphological development and implantation in pigs. Furthermore, we investigated the function of PAG-2 in vitro and found that PAG-2 can inhibit trophoblast cell proliferation and migration. Our analysis provides a valuable resource for understanding the mechanisms of conceptus development and implantation in pig.